Recent Progress in ECDSA and DSA Digital Signature Algorithms - Gong, Senyi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Digital signatures are essential for verifying the authenticity and integrity of information, thus facilitating digital authentication. The Elliptic Curve Digital Signature Algorithm (ECDSA) and the Digital Signature Algorithm (DSA) play critical roles in the field of digital signatures. This paper explores the conceptual frameworks and mathematical underpinnings of these algorithms, providing an in-depth analysis of their advantages and disadvantages with a focus on computational time complexity and key length requirements. The distinct applications of ECDSA and DSA in various fields are examined, highlighting how the selection of an algorithm influences security and efficiency in different scenarios. This analysis also considers the algorithms’ suitability for specific security applications, offering insights into their strategic deployment. By comparing these characteristics, the study aims to guide the selection of appropriate digital signature technology, tailored to meet operational needs and security specifications. This comparative approach not only elucidates the practical implications of each algorithm but also contributes to a broader understanding of their roles in securing digital transactions.